2014
DOI: 10.1128/iai.01104-13
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Mediate Formation of Neutrophil Extracellular Traps in the Middle Ear and Facilitate Secondary Pneumococcal Otitis Media

Abstract: g Otitis media (OM) (a middle ear infection) is a common childhood illness that can leave some children with permanent hearing loss. OM can arise following infection with a variety of different pathogens, including a coinfection with influenza A virus (IAV) and Streptococcus pneumoniae (the pneumococcus). We and others have demonstrated that coinfection with IAV facilitates the replication of pneumococci in the middle ear. Specifically, we used a mouse model of OM to show that IAV facilitates the outgrowth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 46 publications
1
38
0
Order By: Relevance
“…Additionally, NETs are involved in autoimmune vasculitis (53), and impaired NET degradation was associated with lupus nephritis (54). It was recently shown that IgG immune complexes, which are often detected in autoimmune diseases, triggered NET formation (55,56). We observed release of NETs after phagocytosis of IgG-coated bacteria by PMNs as well (data not shown).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Additionally, NETs are involved in autoimmune vasculitis (53), and impaired NET degradation was associated with lupus nephritis (54). It was recently shown that IgG immune complexes, which are often detected in autoimmune diseases, triggered NET formation (55,56). We observed release of NETs after phagocytosis of IgG-coated bacteria by PMNs as well (data not shown).…”
Section: Discussionmentioning
confidence: 52%
“…We observed release of NETs after phagocytosis of IgG-coated bacteria by PMNs as well (data not shown). As such, IgG-induced NET formation most likely plays a role in systemic immunity, but has also been demonstrated to contribute to development of autoimmunity (55,56). Furthermore, activation of the classical complement pathway by IgG and additional opsonization of bacteria with complement factors may contribute to activation of neutrophils and NET formation in the circulation or in interstitial fluids where IgG is the main Ab type.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that NETs trap and efficiently kill microbial pathogens, it is also known that several bacteria, including Staphyloccocus aureus, Streptococcus pneumoniae, Streptococcus suis and Neisseria meningitidis can resist the antimicrobial effect of NET structures, and that this evasion mechanism could be attributed to the production of nucleases able to degrade these NETs, or alternatively to modification or expression of molecules on their membrane or cell wall that could interfere with them (Short et al, 2014;Narayana Moorthy et al, 2013;de Buhr et al, 2014;Berends, et al, 2010;Lappann et al, 2013). Herein, we observed that the production of NETs was unable to kill P. brasiliensis yeasts efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…14 With B cell-deficient infant mice, antibodies were found to play a crucial role in facilitating Spn replication 78 due to antibodydependent NET formation in the ME, which, instead of clearing the infection, allows the bacteria to replicate. It remains unclear whether the OM-inducing antibodies were natural low-affinity antibodies or high-affinity antibodies produced in response to non-Spn antigens or autoantibodies.…”
Section: Cd4mentioning
confidence: 99%